Financial Distress Perusahaan Transportasi Logistik ISSI: Peran Altman Z-Score dan Islamic Social Reporting - Windi Astuti (Jurnal Aplikasi Perpajakan, 2025)
This study aims to determine the effect of the Altman Z-Score prediction model and Islamic Social Reporting (ISR) on financial distress in transportation and logistics companies listed on the Indonesia Sharia Stock Index (ISSI). This study uses a descriptive quantitative approach with secondary data. The research population consists of all public companies engaged in the transportation and logistics sector listed on the Indonesia Sharia Stock Index (ISSI), totaling 28 companies in the period from 2020 to 2022. The research sampling method used purposive sampling, yielding 11 companies or 33 observation data. The analysis technique used in this study was multiple regression analysis. The results of this study show that both partially and simultaneously, Altman Z Score and Islamic Social Reporting (ISR) have a significant effect on Financial Distress. These two variables can explain 71% of financial distress, while the other 29% is explained by variables not mentioned in this study.